QUIZLET’S POWER TO BOOST SEVENTH - GRADE STUDENTS’ VOCABULARY OF DESCRIPTIVE TEXT IN JUNIOR HIGH SCHOOL - Yuana Indah Sriati; Miza Rahmatika Aini; Fadhilawati, Dian (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2023)
In this study, the researchers intended to seek how effective the Quizlet application was at boosting the 29 seventh-grade students’ vocabulary proficiency, especially in defining the words, finding synonyms and antonyms of the words, and using the vocabulary in the context of the descriptive text. The pre-experimental study utilized a one-group pretest-post-test design conducted by the researchers. The research procedures covered three pivotal steps: 1) pre-test, 2) treatment, and 3) post-test. For gaining the desired data objective test was implemented in this study. Before administering the test to the participants, it was tried out at the same level to determine the test's reliability and validity. The data analysis of this study by utilizing Paired sample t-test with SPSS. The results revealed that the student's learning outcome in learning the vocabulary of descriptive text increased from the pre-test score of 66.20 to 85.58. Additionally, it was discovered that the 2- tailed sig value is less than 0.05. It showed that the learning results in the pre-test and post-test data change significantly. Therefore, it might be inferred that Quizlet application is useful for improving the learning outcomes of seventh-grade students, in terms of acquiring the vocabulary of descriptive text. From the result, it is suggested that educators apply Quizlet application to introduce difficult terms in fun and interesting ways.